Why do stroke survivors not receive recommended amounts of active therapy? Findings from the ReAcT study, a mixed-methods case-study evaluation in eight stroke units - Clarke, David; Burton, Louisa-Jane; Tyson, Sarah F.; Rogers, Helen; Drummond, Avril E.R.; Palmer, Rebecca; Hoffmann, Alex; Prescott, Matthew; Tyrrell, Pippa; Brkic, Lianne; Forster, Anne (SAGE, 2018)
Objective: To identify why the National Clinical Guideline recommendation of 45 minutes of each appropriate therapy daily is not met in many English stroke units.